Gaze fixation deficits and their implication in ataxia–telangiectasia. Issue 8 (8th April 2009) - Shaikh, A G; Marti, S; Tarnutzer, A A; Palla, A; Crawford, T O; Straumann, D; Taylor, A M; Zee, D S
Abstract : Background and aim: Ataxia–telangiectasia (A-T) is an autosomal recessive disorder characterised by progressive neurological deficits, including prominent ocular motor dysfunction. Unstable fixation often leads to difficulty reading and blurred vision. Here we characterise the disturbance of visual fixation in A-T. Methods: Eye movements were recorded from 13 A-T patients (with dual search coils in five patients and video oculography in seven) during attempted fixation. Results: Two abnormalities—nystagmus and saccadic intrusions—were common. Horizontal, vertical and torsional nystagmus was present in straight ahead (spontaneous nystagmus) and eccentric gaze (gaze evoked nystagmus). In eight patients the horizontal nystagmus changed directions—periodic alternating nystagmus (PAN). Two types of saccadic intrusions were seen—micro-saccadic oscillations (SO) and square wave saccadic intrusions (SWSI). SO were small amplitude (0.1–0.9°) and high frequency (14–33 Hz) back to back horizontal saccades. SWSI ranged between 1° and 18° (median 3°) with an intersaccadic interval ranging between 50 and 800 ms (median 300 ms). The potential impact of abnormal gaze stabilisation on vision was quantified. Discussion: Degeneration of cerebellar Purkinje neurons disinhibit the caudal fastigial oculomotor region (FOR) and vestibular nuclei (VN). Disinhibition of VN can cause nystagmus, including PAN, while disinhibition of FOR can affect saccade generating mechanisms, leading to SWSI and SO.